Ecological economics and sustainable development selected essays of Herman Daly - Daly, Herman E.; Edward Elgar Publishing (Cheltenham ; Northampton, Mass. : Edward Elgar, 2007)
Ecological Economics and Sustainable Development comprises a carefully chosen selection of some 25 articles, speeches, congressional testimonies, reviews, and critiques from the last ten years of Herman Daly's ever-illuminating work.
Basic concepts and ideas -- Limits to growth -- Economics in a full world -- The challenge of ecological economics : historical context and some specific issues -- Issues with the World Bank -- Sustainable development : definitions, principles, policies -- The illth of nations : comments on World Bank world development report, 2003 -- Can we grow our way to an environmentally sustainable world? -- Issues in ecological economics and sustainable development -- Consumption and welfare : two views of value added -- ecological economics : the concept of scale and its relation to allocation, distribution, and uneconomic growth -- Sustaining our commonwealth of nature and knowledge -- The steady-state economy and peak oil -- How long can neoclassical economists ignore the contributions of Georgescu-Roegen? -- Testimony and opinion -- Off-shoring in the context of globalization -- Invited testimony to Russian Duma on resource taxation -- Involuntary displacement : efficient reallocation or unjust redistribution? -- Sustainable development and OPEC -- Reviews and critiques -- Can Nineveh repent again? -- Beck's case against immigration -- Hardly green -- The return of Lauderdale's paradox -- When smart people make dumb mistakes -- Globalization -- Globalization versus internationalization, and four reasons why internationalization is better -- Population, migration, and globalization -- Philosophy and policy -- Policy, possibility, and purpose -- Feynman's unanswered question -- Roefie Hueting's perpendicular "demand curve" and the issue of objective value -- Conclusions.
Includes bibliographical references and index.
Keywords: Environmental economics; Sustainable development; Electronic books